PENILAIAN PEDESAAN PARTISIPATIF (PRA) UNTUK PERIKANAN TANGKAP SAMBA YANG BERKELANJUTAN DI DESA SABALANA - Nurfadilah, Nurfadilah; Auliansyah, Auliansyah; R, Muhammad Syahrir; Ihsan, Fadhli Insani; Zuhrizal, M.; Utam, Pratita Budi (Jurnal Abdi Insani, 2024)
The people of Sabalan village mostly make a living as fishermen and have three important marine ecosystems. Fishermen usually use various types of fishing gear that are operated in the ecosystem, especially samba trawls used on coral reefs. The implementation of the service is carried out in phase I on January 21, 2022 and phase II on February 3 - 5 2022, in Sabalana Village. In the first stage this activity was carried out to introduce the community to the activities to be carried out and in the second stage data collection activities using the PRA method in the form of fishery profile data and information on samba fishing gear. In this service, it was found that the people of Sabalana Village who mainly work as fishing and cultivating fishermen with fishing locations around the waters of Sabalana Village. The fishing gear used is samba trawl, gill nets, arrows, traps, and fishing rods with various types of catch, the results of which will be processed into dried fish because the location for selling fresh fish is very far from the village. A large number of catches were obtained on samba trawl fishing gear. The use of samba trawler fishing gear is almost the same as the operation of a beach trawler, but Sabalan fishermen have begun to modify the equipment to become samba rere.